DIAGNOSIS AND RECOMMENDATION INTEGRATED SYSTEM (DRIS) NORMS FOR APPLE CV. STARKING DELICIOUS - S. K. ATTAR; N. K. JOOLKA (The Bioscan, 2015)
The Diagnosis and Recommendation Integrated System (DRIS) is an important tool for diagnosing the nutrient balance of the fruit trees and recommending fertilizer schedule for increasing fruit yield and fruit quality. The objectives of this study were to establish DRIS norms for apple (Malus x Domestica Borkh.) and to compare them with norms derived from average of published sufficiency ranges. The study covered the major apple growing belts viz.Jubbal-Kotkhai, Karsog, Kalpa, Kotgarh and Naggar areas of Himachal Pradesh and the orchards were selected for their high productivity and employment of excellent management techniques. The concentrations of nitrogen, phosphorus, potassium, calcium, magnesium, iron, manganese, copper and zinc were determined in leaf samples. The data were divided into high-yielding (>150kg/tree) and low-yielding (<150kg/tree) subpopulations and norms were computed using standard DRIS procedures. The results elucidate that the DRIS model for apple, developed in this study, is a diagnostic tool that may be used to predict if insufficiencies or imbalances in N, P, K, Ca, Mg, Fe, Mn, Cu and Zn supplies are occurring in apple production areas in the Western Himalayas and indeed elsewhere with similar c1imatic and soil conditions.